Everolimus and Early Calcineurin Inhibitor Withdrawal: 3‐Year Results From a Randomized Trial in Liver Transplantation. Issue 3 (6th February 2014) - Sterneck, M.; Kaiser, G. M.; Heyne, N.; Richter, N.; Rauchfuss, F.; Pascher, A.; Schemmer, P.; Fischer, L.; Klein, C. G.; Nadalin, S.; Lehner, F.; Settmacher, U.; et al.
<x xml:space="preserve">Abstract</x> The feasibility of de novo everolimus without calcineurin inhibitor (CNI) therapy following liver transplantation was assessed in a multicenter, prospective, open‐label trial. Liver transplant patients were randomized at 4 weeks to start everolimus and discontinue CNI, or continue their current CNI‐based regimen. The primary endpoint was adjusted estimated GFR (eGFR; Cockcroft‐Gault) at month 11 postrandomization. A 24‐month extension phase followed 81/114 (71.1%) of eligible patients to month 35 postrandomization. The adjusted mean eGFR benefit from randomization to month 35 was 10.1 mL/min (95% confidence interval [CI] −1.3, 21.5 mL/min, p = 0.082) in favor of CNI‐free versus CNI using Cockcroft‐Gault, 9.4 mL/min/1.73 m2 (95% CI −0.4, 18.9, p = 0.053) with Modification of Diet in Renal Disease (four‐variable) and 9.5 mL/min/1.73 m2 (95% CI −1.1, 17.9, p = 0.028) using Nankivell. The difference in favor of the CNI‐free regimen increased gradually over time due to a small progressive decline in eGFR in the CNI cohort despite a reduction in CNI exposure. Biopsy‐proven acute rejection, graft loss and death were similar between groups. Adverse events led to study drug discontinuation in five CNI‐free patients and five CNI patients (12.2% vs. 12.5%, p = 1.000) during the extension phase. Everolimus‐based CNI‐free immunosuppression is feasible following liver transplantation and patients benefit from sustained preservation of renal function versus patients on CNI for at least 3 years.